AN ANALYSIS OF FIGURATIVE LANGUAGE AND MORAL VALUE IN ROAR SONG BY KATY PERRY - Bejo Sutrisno; Lestari Lestari (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
This research is aimed to analyze the figurative languages used in Roar song by Katy Perry. Objectives of the study: (1) to find out the figurative languages used in Roar song by Katy Perry, (2) to find out the meaning of figurative language used in Roar song by Katy Perry, and (3) to find out the moral value messages of the song lyrics. Based on the objective of the study, the researcher uses descriptive qualitative method in collecting the data. From the data analysis, the researcher found out of figurative language appeared in Roar song by Katy Perry. They are Metaphor, Personification, Simile, Paradox, Irony, Alliteration, Onomatopoeia and Hyperbole. It can be implied that figurative language is always used in song lyrics. In Roar song lyrics, there can find moral value massages that can be learned in by the figurative language shown in this song. That is trusting ourself, never doubt to ourself and believe that we have power to refuse some of bad thins comes to our life such as bullying and toxic relationship.